Atos infracionais: uma análise da execução das medidas socioeducativas (Sistema Nacional de Atendimento Socioeducativo - SINASE) - Silva, Pablo Cavalcante e (2010)
This Study approaches the subject of the illegal acts committed by teenagers e the regulation of the execution of socioeducational measures. Through bibliographic research, we made a historical approach of the juridical infancy and youth situation in Brazil and in the World. This way, it was detected a relevant evolution in this area, having the children and the teenagers been elevated to the role of individuals of rights and duties and their protection started to be duty of their families, society and the state. In Brazil, this change happened through the reception of the complete protection doctrine by the Federal Constitution of 1988 and by the Statute of child and adolescent, already approached by the Universal Declaration on the Rights of the Child (1959). From the Statute of child and adolescent, were defined the illegal act and socioeducational measure concepts. Moreover, were contemplated the aspects that involve the investigation of the practice of illegal act and his agents liability. The fact of adolescents been non-attributable in the terms of the criminal legislation but blamed in the terms of the Statute through socioeducational measures, pedagogical sanctions, may induce the society to think that the teenagers that practice illegal acts aren’t punished. The propagation by the media of the idea of an apparent impunity has caused several requests for the anticipation of the penal age, although this isn’t the practicable solution to battle violence in Brazil. At the core of the discussion of implementation of socio-educational measures in Brazil, arises the national system of socioeducational care, product of the parliament law project nº 1627/07 that disposes about the system of socioeducational care, regulates the execution of the measures destined to adolescents that practiced illegal acts and changes Statute’s articles. Moreover, was analyzed the national system of socioeducational care viability as solution to the youth delinquency in Brazil, having as parameters the current legislation and as samples collected data at the units destined to the socioeducational measures compliance in Fortaleza (CE).